ETHNO-MEDIATION IN CONFLICT PREVENTION: AN INSIGHT ON THE COUNCIL OF AKSAKALS AND THE COUNCIL OF MOTHERS - Abylgazina, Kuralay; Abirbek, Sauryk; Onyinyechi Doris Chima (Nazarbayev University Graduate School of Public Policy, 2024)
This study examines the role of traditional councils, in particular the Council of Aksakals and Mothers, in ethnomediation and conflict prevention in Kazakhstan. It focuses on the events in Kordai district in 2020 to analyze the extent to which state policies, media narratives, and public perceptions converge or diverge in their approaches to resolving interethnic tensions. Using a qualitative methodology, the study includes analysis of state policies, media discourse, and interviews with local residents, government officials, and experts to assess the effectiveness and challenges of existing conflict management mechanisms. The results reveal significant gaps between centralized and formalized state policies, media criticism of their rigidity and delays, and public trust in informal mechanisms based on cultural traditions. State policies emphasize national unity and integration through formal structures such as the Assembly of the People of Kazakhstan, while the media highlights socio-economic inequalities and lack of responsiveness. Local communities trust the Councils of Aksakals and Mothers for their local mediation efforts, but acknowledge their limitations due to the lack of institutional support...
Keywords: Type of access: Open; ETHNO-MEDIATION; AKSAKALS; COUNCIL OF MOTHERS